The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/sdi.12116
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Buttonhole Cannulation Practices and Outcomes

Abstract: Buttonhole (constant site) cannulation has emerged as an attractive technique for needling arteriovenous fistulae. However, the balance of benefits and harms associated with this intervention is unclear. We conducted a systematic review of studies reporting outcomes with buttonhole cannulation. The setting and population included adult patients receiving home or center hemodialysis. We searched MEDLINE, Embase (1980-June 2012), and CINAHL (1997-June 2012), for randomized and observational studies. We also sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 44 publications
0
39
0
6
Order By: Relevance
“…Patients have reported less pain on needling and that button hole access does not lead to the aneurysmal dilatation and disfigurement that may occur with area puncture needling (Supplemental figure). However more recently a number of reports of increased infections associated with the buttonhole technique have been published , and as such meta‐analyses have concluded that the buttonhole cannulation technique is associated with higher risk of infection, but further confirmatory studies are required , as a number of studies did not report increased local infection or systemic bacteremia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients have reported less pain on needling and that button hole access does not lead to the aneurysmal dilatation and disfigurement that may occur with area puncture needling (Supplemental figure). However more recently a number of reports of increased infections associated with the buttonhole technique have been published , and as such meta‐analyses have concluded that the buttonhole cannulation technique is associated with higher risk of infection, but further confirmatory studies are required , as a number of studies did not report increased local infection or systemic bacteremia .…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been several subsequent studies reporting a higher rate of infection associated with button hole fistula access compared with, sharp needle area puncture techniques . Recent systematic reviews have concluded that buttonhole cannulation may be associated with a higher rate of local infection and bacteremia compared with area puncture needling, but that more definitive studies are required for a firm conclusion , as some studies have not noted any increase in systemic infections from button hole needling . Infection is not the only complication of buttonhole needling, and observational studies have failed to prove a longer fistula survival time for the buttonhole technique compared to standard rope ladder needling .…”
mentioning
confidence: 99%
“…The rate of local and systemic infection was higher with buttonhole than rope-ladder technique. 10,11 Nonetheless, there are vascular access or patient conditions where one technique may be preferred over the other. Clinicians must consider the pros and cons when making a decision on cannulation strategy and communicate their selection clearly to the dialysis center.…”
Section: Methods Of Cannulation Area Technique Rope-ladder and Buttonmentioning
confidence: 99%
“…However, several studies have reported medium-high risks of local and systemic infection, sometimes with serious complications, occurring at times because of the lack of appropriate disinfection protocols and preventive measures [16,17]. Although BH cannulation offers wellknown advantages such as low infiltration rate, fewer hematomas and less aneurysm formation [18], it still remains of difficult access in the presence of deep vessels, and non-feasible in specific anatomic sites (i.e., arterialized upper arm basilic vein). Only two reports have been published on VWING use.…”
Section: Discussionmentioning
confidence: 99%